Here's the question you clicked on:
aboveit
Which equation is equivalent to 5x-2(7x+1)=14x A. -9x-2=14x B. -9x+1=14x C. -9x+2=14x D. 12x-1=14x I don't understand how I solve it. An explanation or steps would be most appreciated.
|dw:1335226137858:dw| sorry for the cruddy handwriting.
5x-2(7x+1)=14x 5x - 14x-2 =14x -9x-2 = 14x
Simply do algebraic multiplication of the terms inside the parenthesis. So your steps would be 1) 5x - 2(7x+1) 2) 5x -[ (2*7x) + (2*1)] 3) 5x - [14x + 2] (the subtraction sign before the squared bracket means everything inside the bracket will be multiplied by '-1] 4) 5x - 14x -2 5) -9x -2 Hence the answer for this is 'A'